2003
DOI: 10.1892/0891-6640(2003)017<0326:feimlc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Feline Epitheliotropic Intestinal Malignant Lymphoma: 10 Cases (1997–2000)

Abstract: The clinical, histopathologic, and immunohistochemical features of 10 cats with epitheliotropic intestinal malignant lymphoma (EIL) are described. Intestinal biopsy samples were reviewed by 3 pathologists to confirm the diagnosis of EIL. These samples (n = 10) were compared to the intestinal biopsies of normal cats (n = 11), cats with inflammatory bowel disease (IBD; n = 7), and cats with non-EIL (n = 9) for quantification and immunophenotyping of intraepithelial lymphocytes. Immunophenotypic studies were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
33
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 0 publications
1
33
0
1
Order By: Relevance
“…One immunohistological study [27] indicates that infiltration of either T-or B-lymphocytes was observed in the intestine of cats with alimentary lymphoma, whereas both lymphocytic populations infiltrated the intestine of patients with inflammatory bowel disease (IBD). However, another immunohistological study [3] showed that most of the intraepithelial lymphocytes in the intestines were T-cells regardless of whether the cats were histologically diagnosed to have alimentally lymphoma or IBD. Therefore, to confirm the diagnosis of intestinal lymphoma in cats, not only immunohistochemical analysis but also careful morphological evaluation of the degree of mucosal injury and/ or polymerase chain reaction-based clonality assessment of infiltrating lymphocytes are required [13].…”
mentioning
confidence: 99%
“…One immunohistological study [27] indicates that infiltration of either T-or B-lymphocytes was observed in the intestine of cats with alimentary lymphoma, whereas both lymphocytic populations infiltrated the intestine of patients with inflammatory bowel disease (IBD). However, another immunohistological study [3] showed that most of the intraepithelial lymphocytes in the intestines were T-cells regardless of whether the cats were histologically diagnosed to have alimentally lymphoma or IBD. Therefore, to confirm the diagnosis of intestinal lymphoma in cats, not only immunohistochemical analysis but also careful morphological evaluation of the degree of mucosal injury and/ or polymerase chain reaction-based clonality assessment of infiltrating lymphocytes are required [13].…”
mentioning
confidence: 99%
“…Lymphoma is the most common neoplasm in cats, 4,9,12,19,25,28,30,38 accounting for 50 to 90% of all feline hematopoietic neoplasms. 37 Further, since the widespread implementation of test/euthanize and vaccination programs for the control of feline leukemia virus (FeLV), 21,37,38 the gastrointestinal tract (GIT) has been reported by several authors to be the most frequently recognized anatomic location of disease.…”
mentioning
confidence: 99%
“…37 Further, since the widespread implementation of test/euthanize and vaccination programs for the control of feline leukemia virus (FeLV), 21,37,38 the gastrointestinal tract (GIT) has been reported by several authors to be the most frequently recognized anatomic location of disease. 4,12,17,19,28 Cats with GIT lymphoma have a median age of 12 years, 37 and they are generally FeLV negative. 28,37 Most authors report that within the GIT, B-cell tumors predominate over T-cell tumors and tumors of large granular lymphocytes (LGLs).…”
mentioning
confidence: 99%
“…The alimentary form is common in cats [1,5,9,10], but uncommon in dogs, accounting for only 5 to 7% of all lymphomas [2,8]. It is generally believed that full thickness biopsy of the intestine is necessary to diagnose alimentary lymphoma as the lesions are usually deep-seated and invade the serosa.…”
mentioning
confidence: 99%